2011
DOI: 10.1111/j.1365-2702.2011.03809.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors that facilitate and hinder the manageability of living with amyotrophic lateral sclerosis in both patients and next of kin

Abstract: Fluctuations in manageability and similarities and differences between approaches to managing the situation suggest a need for input from caregivers, for the whole family. Family members need support and time for their own needs and also the opportunity to increase their awareness and understanding of the needs of other family members. This study may give health personnel insight into how to help families devise strategies to manage a complex life situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 22 publications
4
44
0
Order By: Relevance
“…Reduced caregiver distress contributes to managing the caregiver's situation and thus decreasing strain 33. In line with these caregiver experiences, our study showed that higher levels of caregiver anxiety were associated with higher levels of caregiver strain.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Reduced caregiver distress contributes to managing the caregiver's situation and thus decreasing strain 33. In line with these caregiver experiences, our study showed that higher levels of caregiver anxiety were associated with higher levels of caregiver strain.…”
Section: Discussionsupporting
confidence: 79%
“…Bakker et al 32 in their qualitative study reported that some patients and caregivers perceived the QOC of their ALS team to be suboptimal. Other studies showed that family members of patients with ALS search for practical and emotional support from their healthcare professionals 13 14 33. Caregivers who experienced the specialist ALS clinic as being supportive, mentioned that this helped them to cope with the situation 34.…”
Section: Discussionmentioning
confidence: 99%
“…It would probably help them in coping with the situation and find meaning in life if they could talk about those kinds of feelings and obtain answers about possible misunderstandings both during the disease process and after the partner had passed away. As shown in this and other studies (see Olsson Ozanne et al, 2012;Ozanne et al, 2013), spouses and partners could find it difficult to talk with each other about their feelings and thoughts. Hence, although it might be preferable to provide individual support for spouses, it is also necessary to give spouses and patients joint support and help each to see the other's situation so that they can be there for each other.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have examined manageability among the spouse-patient pairs and finding meaning among patients (Olsson Ozanne et al, 2012;Ozanne et al, 2013). Our study was performed to reveal experiences of finding meaning among spouses of people living with ALS.…”
Section: Designmentioning
confidence: 98%
“…) and living in the present can facilitate the devising of coping strategies (Gysels & Higginson , Olsson Ozanne et al . ). It might be easier to find acceptance by focusing on what one can achieve instead of what is impossible.…”
Section: Introductionmentioning
confidence: 97%